1994
DOI: 10.5271/sjweh.1429
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory symptoms and bronchial reactivity among pig and dairy farmers.

Abstract: ratory symptoms and bronchial reactivity among pig and dairy farmers. Scand J Work Environ Health 1994;20:48-54. OBJECTI VES -This study assessed the prevalence of respiratory manifestations among French pig and dairy farmers and determined the relationship between bronchial reactivity and respiratory manifestations. METHODS -The pig farmers included 102 men working more than halftime inside swine confinement buildings. There were 51 male dairy farmers and 81 male referents. The demographic characteristics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
43
0
2

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 31 publications
4
43
0
2
Order By: Relevance
“…The low prevalence of chronic bronchitis among the farmers was especially surprising, since this symptom is probably most consistently found to be associated with farming [9][10][11][12][13][14]. One explanation for the current finding is that chronic bronchitis is especially associated with pig farming [14,25,26] and very few farmers of the present study worked in piggeries.…”
Section: Discussionmentioning
confidence: 38%
See 2 more Smart Citations
“…The low prevalence of chronic bronchitis among the farmers was especially surprising, since this symptom is probably most consistently found to be associated with farming [9][10][11][12][13][14]. One explanation for the current finding is that chronic bronchitis is especially associated with pig farming [14,25,26] and very few farmers of the present study worked in piggeries.…”
Section: Discussionmentioning
confidence: 38%
“…One explanation for the current finding is that chronic bronchitis is especially associated with pig farming [14,25,26] and very few farmers of the present study worked in piggeries. In addition, this study was restricted to females, whereas the previous studies showing the association between farming and chronic bronchitis have included either exclusively [9,10] or predominantly [11][12][13] males.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A limited number of studies has been published on the role of bronchial responsiveness. With a few exceptions [15,26,27] most of these were based on small numbers [7,13,29,35,36,48,54] and/or one-dose provocation protocols, in which no degree of response can be assessed [4,45,47], None of the studies on bronchial responsiveness have so far dealt with associ 328 ations between exposure of the pig fanner and the prevalence of hyperresponsiveness. If such associations can be demonstrated, this provides clues for prevention.…”
Section: Introductionmentioning
confidence: 99%
“…Respiratory symptoms [1][2][3], reductions in mean and across shift lung-function values [1,[4][5][6] and increased bronchial responsiveness [3,[7][8][9][10][11][12][13][14] have been described in exposed workers and in naĂŻve volunteers exposed to intensive swine production facilities. In addition to this, SUNDBLAD et al [13] demonstrated that exhaled nitric oxide (NO) increased following exposure only when a half mask was not worn, despite both groups (those wearing and those not wearing a mask) showing increased bronchial responsiveness, suggesting that the two outcome measures reflect different aspects of airway inflammation.…”
mentioning
confidence: 99%